Pengaruh Literasi Keuangan dan Hedonic Consumption terhadap Perilaku Keuangan Mahasiswa Program Studi Manajemen UNISKA MAB Banjarmasin (Studi pada Mahasiswa di Barito Kuala) - Muhammad Abdul Ghani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of financial literacy and hedonic consumption on the financial behavior of Management Study Program students at UNISKA MAB Banjarmasin, Barito Kuala Campus, class of 2022. This research uses a quantitative approach with a causal associative design. The population consisted of 570 active students, and the sample of 85 respondents was determined using the Slovin formula with simple random sampling. Data were collected through a questionnaire measured on a Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics. The results of the partial test (t-test) show that financial literacy has a positive and significant effect on financial behavior (t = 7.449; sig. < 0.001), whereas hedonic consumption has no significant effect (t = 1.973; sig. = 0.052). Simultaneously (F-test), financial literacy and hedonic consumption significantly affect financial behavior (F = 39.069; sig. < 0.001), with an Adjusted R Square of 0.475, meaning that both variables explain 47.5% of financial behavior while the remaining 52.5% is explained by other factors outside this study. These findings confirm that financial literacy is the more dominant cognitive factor in shaping students' financial behavior.